1974
DOI: 10.1021/jo00936a015
|View full text |Cite
|
Sign up to set email alerts
|

Structure of catechinic acid. Base rearrangement product of catechin

Abstract: The pmr spectra of a number of trimethylsilyl ethers of simple alcohols have been reported: H.A. Bruñe, Chem. Ber., 97, 2829(1964. Comparison of their chemical shifts to those of the corresponding alcohols indicate an upfield of shift of the signal for the protons on the oxygenated carbon upon silylation. (12) A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…12(a)) showed the presence of high amounts of epigallocatechin (12) as reported by Nagle et al [39] and Graham [40] as the major catechin found in green tea. Also, similar to the findings of Chen et al [41] epicatechin (10) was the second most abundant flavan-3-ol in green tea. Also, in Fig.…”
Section: Tea Leavessupporting
confidence: 89%
See 2 more Smart Citations
“…12(a)) showed the presence of high amounts of epigallocatechin (12) as reported by Nagle et al [39] and Graham [40] as the major catechin found in green tea. Also, similar to the findings of Chen et al [41] epicatechin (10) was the second most abundant flavan-3-ol in green tea. Also, in Fig.…”
Section: Tea Leavessupporting
confidence: 89%
“…Another remarkable result of the THM-GC-MS of catechin (trans epimer) and epicatechin (cis epimer) was the large retention time difference between partially methylated catechin (8) and epicatechin (10). On THM of epicatechin product 10 (not shown) was the dominant peak in the chromatogram, thus, this paper has shown that one can discriminate between epicatechin and catechin using the THM approach of analysis.…”
Section: Thm-gc-ms Of Catechin and Epicatechinmentioning
confidence: 74%
See 1 more Smart Citation
“…Rearrangement products of catechins have also been held responsible for the inhibition of collagen breakdown by collagenases in vitro [32]. Three candidates for active rearrangement products are (+)-epicatechin [12], catechinic acid [27], and quinones.…”
Section: Discussionmentioning
confidence: 99%
“…The quinone methide intermediate is rather labile, and side reactions other than epimerization are thought to occur from this intermediate (Sears et al, 1974;Kennedy et al, 1984). Both epi type catechins and non-epi type catechins are also labile to dimerization (Roginsky et al, 2005), hydrolysis (Ito et al, 2003), oxidation and polymerization (Hatano et al, 2004).…”
Section: Epimerization Behavior Of Tea Catechins and The Effect Of β-Cdmentioning
confidence: 99%